PENAFSIRAN AYAT MUSIBAH DALAM QS. AT-TAGHABUN (Kajian Tafsir Tahlili QS. At-Taghabun Ayat 11) - Muhammad Thohir (CV. KAMPUS AKADEMIK PUBLISING, 2025)
QS. At-Taghabun verse 11 contains important concepts regarding faith and destiny, often serving as a foundation for Muslims in facing life's trials. This article aims to delve deeper into the meaning of calamities from both classical and contemporary tafsir perspectives, and how scholars interpret this verse within the context of Islamic theology. The methodology employed in this research is a qualitative approach with textual analysis from various tafsir books, including Tafsir Al-Misbah by M. Quraish Shihab, Tafsir Ibn Kathir, Tafsir Al-Qushayri, and Tafsir Al-Kabir by Fakhruddin Ar-Razi. This study finds that calamities in QS. At-Taghabun verse 11 are understood as part of Allah's decree imbued with wisdom, urging Muslims to accept calamities with patience and reliance on Him, and to connect every event with Divine will. The conclusion of this research indicates that scholars' interpretations of calamities provide profound insights into understanding them as tests and manifestations of Allah's mercy, ultimately leading individuals to greater spiritual closeness with Him. These findings are expected to contribute to the development of Quranic exegesis studies, particularly in the exploration of verses related to calamities and life's trials.